Liquid Gallium Nanospheres Emitting White Light. Issue 5 (8th April 2019) - Xiang, Jin; Chen, Jingdong; Jiang, Shuai; Panmai, Mingcheng; Li, Peilian; Xu, Yi; Dai, Qiaofeng; Tie, Shaolong; Lan, Sheng
Abstract: Gallium (Ga) is not only a metal possessing surface plasmon resonance in the ultraviolet region but also a phase‐change material with very low melting point. Spherical Ga nanoparticles composed of liquid Ga cores and solid Ga2 O3 shells, which exhibit surface plasmonic resonances spanning the ultraviolet to near‐infrared spectral region, are fabricated by using femtosecond laser ablation. Under the excitation of femtosecond laser light, only second harmonic generation is observed in the Ga nanospheres placed on a glass substrate. In sharp contrast, white light emission can be generated in such Ga nanospheres when they are placed on a thin silver film. It is revealed numerically and confirmed experimentally that a Fano resonance originating from the interference between the mirror‐image‐induced magnetic dipole mode and the gap plasmon mode is formed in the backward scattering spectra of the Ga nanospheres. Efficient white light emission can be achieved by resonantly exciting either the magnetic dipole resonance or the Fano resonance. Based on spectral analysis, the white light emission is identified as the hot‐electron intraband luminescence. The fabricated core–shell Ga nanospheres provide an ideal platform on which the optical properties and practical applications of liquid Ga nanoparticles can be systematically investigated. Abstract : Ga nanospheres with liquid Ga cores and Ga 2 O 3 shells can emit hot‐electron luminescence under the excitation of femtosecond laser pulses when they are placed on a thin Ag film. Efficient white light emission can be achieved by resonantly exciting either the mirror‐image‐induced magnetic dipole resonances or the Fano resonances in the scattering spectra of the Ga nanospheres.